2020
DOI: 10.3341/kjo.2020.0024
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Decrease in Ocular Deviation 1 Day before Surgery in Patients with Intermittent Exotropia

Abstract: Purpose To evaluate the clinical characteristics of patients with intermittent exotropia who exhibited a dramatic decrease in ocular deviation 1 day before surgery. Methods This study retrospectively enrolled patients with intermittent exotropia who underwent surgery between December 2013 and December 2019. Those who exhibited a decrease in ocular alignment ≥10 prism diopters (PD) at the last examination (1 day before surgery) compared with the largest previous angle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Lim and Kim showed a higher possibility of dramatic decreases in ocular alignment before impending surgery caused by anxiety in pediatric patients with controllability [ 12 ]. These patients had relatively better level of control [ 12 ]. Lee et al reported better surgical outcomes of exotropia in patients with increased ocular deviation after the monocular occlusion test [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lim and Kim showed a higher possibility of dramatic decreases in ocular alignment before impending surgery caused by anxiety in pediatric patients with controllability [ 12 ]. These patients had relatively better level of control [ 12 ]. Lee et al reported better surgical outcomes of exotropia in patients with increased ocular deviation after the monocular occlusion test [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with controllability showed a relatively later onset of exotropia than those without controllability, possibly because patients with better binocularity can maintain normal ocular alignment for a longer time, leading to older mean ages of onset and surgery. Similarly, patients with better binocularity may hide the total amount of ocular exodeviation, leading to variability in ocular exodeviation during follow-up [11][12][13]. Lim and Kim showed a higher possibility of dramatic decreases in ocular alignment before impending surgery caused by anxiety in pediatric patients with controllability [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may increase anxiety, which in turn leads to a temporal increase in the level of control and a decrease in ocular deviation. The level of control in pediatric patients with controllability may be easily affected by intrinsic factors, such as anxiety, and may result in a decrease in ocular deviation at initial examination [ 4 ]. Clinicians should be aware of the possibility of hidden ocular deviation, especially in pediatric patients with controllability.…”
Section: Discussionmentioning
confidence: 99%
“…The level of control is associated with fusional capacity and variability in the exodeviation of patients with intermittent exotropia [ 3 ]. The level of control in patients with intermittent exotropia can be affected by several factors including general health, alertness, attention span, and level of anxiety [ 1 , 4 ]. The results of the MO may be affected by and differ according to the level of control [ 3 ].…”
mentioning
confidence: 99%